Canais de acesso à informação disponibilizados aos alunos sob a responsabilidade social da Fundação Bradesco - Machado, Alecsandra Coutinho (2012)
The theme of this research focuses on the social role of information science with emphasis on access to information as a fundamental element of information management and relevance to the process of social and organizational. It aims to analyze the channels of access to information for the social inclusion of young people assisted by social responsibility programs of Fundação Bradesco. Methodologically, characterized as qualitative research of descriptive level. Adopts as a tool for data collection structured interviews in focus groups. Data were summarized in tables and mind maps recorded by means of symbols and messages. The presentation of results in the form of maps is considered a technique adopted by meaningful learning. For data analysis, we adopted the technique of content analysis. The previously developed instrument consisted of four parts: socio economic students' information channels used in the institutional environment, channels adopted in another environment and other forms of obtaining information. The results indicate that the socioeconomic characteristics of the students are in line with the precepts of the Information Society and social responsibility program of the institution for those most in need, irrespective of age and gender, prioritizing economic conditions for access . The results indicate that there is an available channel information, and the information accessed via these channels have an effective contribution provided by social responsibility programs of Fundação Bradesco for social inclusion of students through formal learning.